The Influence of Work Motivation, Reward, Work Environment, and Job Satisfaction on Employee Performance in Concrete Iron Companies in Indonesia - Angela Jovita Listyarini; Sukmo Hadi Nugroho (Petra International Journal of Business Studies, 2025)
Work Motivation plays a crucial role in driving employees to contribute effectively to a company. Reward and Work Environment act as key supporting elements that help employees attain job satisfaction and enhance their performance. This study aims to examine how Work Motivation, Reward, Work Environment, and Job Satisfaction influence Employee Performance within Concrete Iron Companies in Indonesia. The research utilized a saturated sample method, involving all staff employees in the concrete iron industry, with a total of 180 respondents. Data analysis was performed using the Structural Equation Model (SEM) method using SmartPLS 3.29. The findings indicate that Reward positively influences both Work Motivation and Job Satisfaction. Additionally, Work Environment and Work Motivation both positively affect Job Satisfaction. Furthermore, Work Motivation and Job Satisfaction each have a positive impact on Employee Performance, as does Work Environment. The managerial implication of this research highlights the importance of fostering work motivation, job satisfaction, and employee performance among employees to generate overall positive outcomes for the company.